Further Understanding of Nitrogen-Doped Carbon Catalytic Property towards Oxygen Reduction Reaction (ORR). (2016) - Merzougui, Belabbes; Bukola, Saheed; Zaffou, Rachid
Abstract: Nitrogen functionalities such as pyridinic-nitrogen, pyrrolic-nitrogen and graphitic-nitrogen based active sites are commonly produced when nitrogen precursors are pyrolyzed on carbon matrix. In this study, we demonstrate two catalysts prepared via pyrolysis of Polyaniline and Vinazene with carbon. Their excellent Oxygen reduction reaction (ORR) activities and potential cycling stability were confirmed using thin film rotating ring-disk electrode (RRDE) in 0.1 M KOH and 0.1 M HClO4 . Structural-performance correlation analysis confirms that not only graphitic nitrogen is responsible for high ORR, but also other nitrogen functions including pyrrolic one. However, catalyst that is rich in graphitic-N shows more stability especially in acidic medium.